2022
DOI: 10.1080/2374068x.2022.2037352
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and hardness of rapidly solidified hypereutectic Al-Si surface layers by laser remelting

Abstract: A laser rapid solidification technique was employed to remelt and refine the microstructure of Al-25wt.%Si and Al-30wt.%Si alloyed layers produced by laser melting. The microstructure of the as-fabricated Al-Si layers consisted of irregular polygonal primary Si crystals of size 5 to 7 µm, fine α-Al dendrites, and Al-Si eutectic. Laser rapid remelting results showed a significant refinement of all the solidified phases with increasing scan speed and decreasing laser power. At the lowest laser power (800W), the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Figure 10 illustrates the change curve of the friction curve and friction coefficient of hypoeutectic Al-9Si alloy after treatment with different pulse frequencies. The friction coefficient reflects the contact state between friction and wear materials [31], and its magnitude is influenced by load, contact area, and lubrication [32]. It is observed that the friction curve of the sample following high-frequency pulse treatment exhibits a stable and gradual trend, with an average value of the optimal friction coefficient at 0.3 ± 0.01.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Figure 10 illustrates the change curve of the friction curve and friction coefficient of hypoeutectic Al-9Si alloy after treatment with different pulse frequencies. The friction coefficient reflects the contact state between friction and wear materials [31], and its magnitude is influenced by load, contact area, and lubrication [32]. It is observed that the friction curve of the sample following high-frequency pulse treatment exhibits a stable and gradual trend, with an average value of the optimal friction coefficient at 0.3 ± 0.01.…”
Section: Mechanical Propertymentioning
confidence: 99%